2005
DOI: 10.1289/ehp.7598
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Prediction of the Response of Freshwater Fish to a Mixture of Estrogenic Chemicals

Abstract: Existing environmental risk assessment procedures are limited in their ability to evaluate the combined effects of chemical mixtures. We investigated the implications of this by analyzing the combined effects of a multicomponent mixture of five estrogenic chemicals using vitellogenin induction in male fathead minnows as an end point. The mixture consisted of estradiol, ethynylestradiol, nonylphenol, octylphenol, and bisphenol A. We determined concentration–response curves for each of the chemicals individually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
237
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 351 publications
(255 citation statements)
references
References 47 publications
16
237
0
2
Order By: Relevance
“…Considering the estrogenic potencies of chemicals varying with species and bioassay endpoint, the potency values obtained from the two-hybrid yeast assay for individual substances were compared with those reported in the literature using other methods. We found that our estrogenic activity order for the test chemicals was close to, and the EC 50 values were slightly lower than most of the published ones (Brian et al, 2005;Correia et al, 2007;Folmar et al, 2002;Liu et al, 2009;Thorpe et al, 2005), which illustrates the reliability and high sensitivity of our yeast strain.…”
Section: Discussionsupporting
confidence: 62%
“…Considering the estrogenic potencies of chemicals varying with species and bioassay endpoint, the potency values obtained from the two-hybrid yeast assay for individual substances were compared with those reported in the literature using other methods. We found that our estrogenic activity order for the test chemicals was close to, and the EC 50 values were slightly lower than most of the published ones (Brian et al, 2005;Correia et al, 2007;Folmar et al, 2002;Liu et al, 2009;Thorpe et al, 2005), which illustrates the reliability and high sensitivity of our yeast strain.…”
Section: Discussionsupporting
confidence: 62%
“…For example, EE2 and 17-trenbolone, a synthetic steroidal androgen used in livestock, are quite analogous in that they both impact the reproductive endocrine system of fish at very low yet environmentally relevant (nanograms-per-liter) concentrations in the water (8,14,15). However, current testing approaches would consider their ecological risks differently.…”
mentioning
confidence: 99%
“…There are evidences that estrogenic compounds act either additively (Brian et al, 2005) or mildly synergistically (Christiansen et al, 2009). If we assume the two EDCs do not interact with each other, the ORP for exposure to the mixture of two is P m = 1 -(1 -0.081) (1 -0.27) = 0.33 Equation (17) On the other hand, if we use a synergistic coefficient of 0.10 to represent the interacting effect of the two, the ORP for exposure to the mixture is 1 -P E2 = (1 -0.081) (1 -0.10 x 0.27) = 0.894 Equation (18a) 1 -P EE2 = (1 -0.27) (1 -0.10 x 0.081) = 0.724 Equation ( …”
Section: Some Numerical Examples To Illustrate the Use Of The Techniquementioning
confidence: 99%